From playing to being responsibility: implementation of 21st-century learning for digital media ethics in elementary schools - Lieza, Tarina Nurul; Karlina, Yayang; Iskandar, Sofyan (Universitas Tanjungpura, 2026)
The rapid development of digital technology has brought new challenges in education, especially regarding the understanding and application of digital media ethics by students in elementary school. The implementation of 21st-century learning, which currently emphasizes critical thinking, creativity, collaboration, communication, character, and citizenship (6C) skills, is an effective strategy for instilling digital media ethics from an early age. This article examines a game-based learning model integrated into learning to shape responsible attitudes in the digital interactions of elementary school students. The research method used is a literature study from various journals discussing the ethical use of digital media in the implementation of 21st-century learning in elementary schools. The results of the analysis show that learning with a play-based approach and interactive simulations can increase students' awareness of the social impact of digital media and strengthen ethical digital literacy skills. In addition, the role of teachers as facilitators and the involvement of parents in digital supervision have proven to be significant in the successful implementation of this program. These findings are in line with previous studies that highlight the importance of integrating 21st- century learning in basic education to build the digital character of smart and responsible students. The contribution of this article lies in presenting a practical and contextual approach to developing digital media ethics through learning that combines play and social responsibility in elementary schools.